Overall view of chemical and biochemical weapons - Pitschmann, Vladimír (Toxins, 2014)
This article describes a brief history of chemical warfare, which culminated in the signing of the Chemical Weapons Convention. It describes the current level of chemical weapons and the risk of using them. Furthermore, some traditional technology for the development of chemical weapons, such as increasing toxicity, methods of overcoming chemical protection, research on natural toxins or the introduction of binary technology, has been described. In accordance with many parameters, chemical weapons based on traditional technologies have achieved the limit of their development. There is, however, a big potential of their further development based on the most recent knowledge of modern scientific and technical disciplines, particularly at the boundary of chemistry and biology. The risk is even higher due to the fact that already, today, there is a general acceptance of the development of non-lethal chemical weapons at a technologically higher level. In the future, the chemical arsenal will be based on the accumulation of important information from the fields of chemical, biological and toxin weapons. Data banks obtained in this way will be hardly accessible and the risk of their materialization will persist.
Keywords: Public Policy; chemická válka; Chemical Warfare; Animals; mezinárodní spolupráce; Humans; Toxicity Tests; testy toxicity; Chemical Warfare Agents; Biological Warfare Agents; vojenská věda; Military Science; dějiny 21. století; Nanotechnology; chemické bojové látky; chemické látky k potlačení nepokojů; nanotechnologie; zvířata; Riot Control Agents, Chemical; veřejná politika; dějiny středověku; History, Medieval; International Cooperation; dějiny 20. století; lidé; History, 20th Century; History, 21st Century; biologické bojové látky